Types of flouting maxim in lady bird movie - Dewi, Ni Komang Trisa; Utami, Ni Made Verayanti; Putri , Widiadnya (Institut Pariwisata dan Bisnis Internasional, 2020)
The aim of this study was to find out types of flouting maxim in Lady Bird movie by using theory conduct by Grice (1975). The data was collected from Lady Bird movie, this movie talked about teenager’s life. The data were collected by using library analysis method and analyzed by descriptive and qualitative method. The finding is presented in formal and informal way. Our findings show that there are four types were performed by the characters in Lady Bird movie. There were flouting maxim of quantity (47,7%), flouting maxim of quality (28,7%), flouting maxim of relevance (19%) and flouting maxim of manner (4,6%).